1985
DOI: 10.1007/bf00017971
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies in dynamic fracture mechanics

Abstract: This paper provides a summary of recent studies concerning numerical modeling of dynamic crack-propagation. Both "stationary mesh" as well as "moving mesh" finite-element procedures are examined. Simple procedures, using a moving mesh of conventional isoparametric elements in conjunction with certain path-independent integrals for the evaluation of stress-intensity factors for a dynamically propagating crack are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…where E * is the e ective Young's modulus proposed by Cherapanov: (12) where t , n , and f are strains measured close to the crack front along the tangent, normal, and binormal to the crack front (surface). The dynamic fracture toughness is a function of the crack speed given by…”
Section: Physical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where E * is the e ective Young's modulus proposed by Cherapanov: (12) where t , n , and f are strains measured close to the crack front along the tangent, normal, and binormal to the crack front (surface). The dynamic fracture toughness is a function of the crack speed given by…”
Section: Physical Modelmentioning
confidence: 99%
“…The moving mesh technique was used by Atluri and Nishioka 12 (with the FEM), Koh, Lee and Haber 13 (Eulerian-Lagrangian description in conjunction with the FEM), Gallego and Dominguez 14 (BEM with a moving singular element), Koh et al, 15 (Eulerian-Lagrangian description in conjunction with the FEM). Modelling arbitrary curved crack growth seems to be di cult with this approach, since excessive mesh distortion will occur.…”
Section: -D Crack Growth Simulationsmentioning
confidence: 99%
“…Due to the aforementioned difficulties, the finite element method has been mostly limited to two-dimensional problems with the crack confined to its original line. While early work focused on various node release techniques and on the development of special singular elements moving with the crack tip (Atluri and Nishioka, 1985), recent work has included the introduction of special adaptive h-p methods for hyperbolic systems (Safjan and Oden, 1993) and of Eulerian-Lagrangian formulations to better cope with the continuously changing geometry (Koh et al, 1988). To study the spontaneous out-of-plane motion of two-dimensional dynamically propagating cracks, Swenson and Ingraffea (1988) used remeshing and interactive graphics to control the mesh distortion, while, more recently, Xu and Needleman (1994) introduced a cohesive surface constitutive relation allowing for the creation of new free surfaces along a family of possible fracture directions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical experimentations have shown that ~ at different increments may vary significantly within a single step. The magnitude of the variation is found to be influenced by types of relaxation techniques discussed in [6]. However, our results show that once the average G for a time step is determined, it is essentially independent of any relaxation techniques.…”
Section: G Calculation With Node Release Techniquementioning
confidence: 46%
“…Some frequently used methods are node release, moving singular element and shifting crack tip node techniques. The overview, including advantages and disadvantages, of these techniques was given by Atluri and Nishioka [6].…”
Section: Introductionmentioning
confidence: 99%